Caracterização da eficiência nutricional em relação ao fósforo em genótipos de batata - Sausen, Darlene (2013)
The objective of this work was to characterize the potato genotypes for phosphorus efficiency evaluated in in vitro and in hydroponics growth systems. Experiments were conducted in in vitro with potato genotypes grown at two P levels, 5 and 50% concentration of MS medium, 1.935 mg P L-1 and 19.346 mg P L-1, respectively. The hydroponic experiment consisted of seven potato genotypes and two doses of P, 5 and 50% of the strength of the nutrient solution developed for soilless cultivation of potatoes (ANDRIOLO, 2006), called as a low (2.32 mg P L-1) and high (23.2 mg P L-1) levels of P. The plants were evaluated in in vitro at 40 days after inoculation and in hydroponic culture at 18, 39 and 62 days after planting. The direct and indirect effects of each variable on the efficiency of utilization of P in potato genotypes are dependent on the condition of cultivation (hydroponic or in vitro), the P concentration and the harvest time. Taken together the efficiency indexes of P utilization, it was possible to characterize that the potato genotypes responded differently to P deficiency in each growth system, with the exception of the SMIJ 319-1 genotype which in the two systems presented efficient in utilization and response to P. The in vitro culture system is not appropriate for the selection of potato genotypes with regard to determining the efficiency of utilization and response to P.